Histomorfometria sazonal epididimária do morcego Artibeus planirostris (Chiroptera: Phyllostomidae) - Araújo, Rodrigo Serafim de (2016)
Considering the ecological importance of the bat Artibeus planirostris and the importance of the epididymal evaluation for the understanding of its reproductive function, this study aimed to understand the reproductive parameters of this species, from the morphological and morphometric analysis of the epididymis. Sixteen adult animals were collected during the dry season (n = 08) and rainy season (n = 08), in 2014. The captures were taken in the city of Natal-RN (5°50'33.9"S and 35°12'07.6"W) (SISBIO authorization no. 25233-1), using mist nets. After anesthesia and euthanasia by transcardiac perfusion, the epididymis were collected (CEUA/UFRN authorization no. 009/2012), followed by histological processing for embedding in historesin and analysis under light microscopy. Morphometric analyzes of the epididymal parenchyma were performed using images from the histological slides, by the Image-Pro Plus software. The results were submitted to ANOVA, and the means were compared by Student's t-test at a significance level of 5%, followed by Tukey's post-test. At the two analyzed seasons, the morphological evaluation showed that the organ was divided into 4 main regions: initial segment, head, body and tail. The parenchyma was predominantly composed of epididymal tubules, supported by intertubular connective tissue. During the three main epididymal portions, the tubules occupied 75.07 ± 2.94 % of parenchyma in rainy season and 67.23 ± 2.44 % in dry season, and its percentages in the head and body were significantly larger in rainy season compared to dry season. The remaining parenchyma was represented by the intertubular region, which showed proportional reduction in the same regions and seasons. The tubules were composed of cylindrical pseudostratified epithelium with stereocilia, supported by a tunica propria and lumen. The epididymal epithelium was the main component of the epididymal tubule. In the tail region, its percentage was higher in dry season (27.58 ± 8.33%) than in rainy season (17.79 ± 4.33%). This epithelium was composed by main (MA), basal (BA), narrow (NA), halo (HA), clear (CL) and apical (AP) cells. The first and the last ones showed, respectively, the highest and the lowest distributions in all epididymal regions, in both rainy and dry seasons. In the head and tail regions, MA cells were the most predominant in the epididymal epithelium in the dry season in relation to the rainy season, while BA cells were the most predominant in the rainy season, such in head as in tail. AP cells had a higher distribution in epididymis head during the rainy season, while NA cells had a greater distribution in the epididymis body during dry season, being its observation in this epididymal portion a new finding. There was an increase in several morphometrical parameters, from the head to the tail, such as the tubular and luminal diameter and its percentages with spermatozoa, as well the muscle cells surrounding the epididymal tubules, in contrast with a decrease in epithelial high. Several of these parameters showed larger values in the rainy season in relation to the dry season. It can be concluded that the epididymis of A. planirostris was similar to that described for other mammals, and the narrow cells were recorded in the region of the body for the first time. It was found spermatozoa in the lumen of epididymal tubules during the two seasons evaluated, especially in the tail region, showing a continuous annual reproductive pattern, with reproductive peaks in the rainy season.